Successful tandem transplant in a young aplastic anemia patient from a small-weight 11-month-old sibling donor. Issue 1 (February 2016) - Arora, Dinesh; Tiwari, Aseem Kumar; Dara, Ravi C.; Misra, Ruchira; Aggarwal, Geet; Acharya, Devi Prasad; Raina, Vimarsh
Abstract: Five years five month old male child diagnosed with aplastic anemia required blood and platelet support regularly. He was advised bone marrow transplant (BMT) and had 6/6 match with a younger sibling (11 months old). He was admitted for planned BMT and was put on preparatory regimen five days prior to BMT. GCSF-primed bone marrow (BM) harvest was done from the donor, but the harvest was insufficient (1.05 × 10^6 /kg) and target dose of 4 million stem cells per kg could not be achieved. The BM harvest was infused into the patient and a repeat BM harvest was contemplated on next day. After careful evaluation of risks and benefits to the patient and the young donor, a decision to do a peripheral blood stem cell (PBSC) harvest was taken. The apheresis kit was blood primed to preclude possible hemodynamic imbalance in the donor considering low weight and young age. The entire harvest procedure (321 minutes) was uneventful with the donor remaining stable throughout. A dose of 2.40 million per kg of CD34+ cells was harvested and infused. Thus, a total dose of 3.45 million (1.05 BM and 2.4 PBSC) per kg was infused into the patient. Neutrophil and platelet engraftments and donor chimerism were achieved successfully with tandem BM-PBSC infusion and the patient continues to be disease free till 180 days follow up. This is possibly first published Indian report on BM-PBSC tandem transplant suggesting safety of PBSC harvests in small-weight young-age donor.